Relationships between parenting styles, parental involvement, and intellectual abilities among preschool children in Putrajaya, Malaysia - Tang, Lee Foong (2019)
Development of intellectual ability is one of the critical aspects of development among preschool children. Children’s intellectual ability is among the most essential predictors for the rest of their academic life. Children with higher intellectual ability or intelligence quotient (IQ) are less likely to be held back a grade in their schooling years, and less likely to have very few friends or rejected by their peers. Furthermore, some of the important and possible factors that may likely to explain the children’s intellectual ability include of: social environment which reflect on how parents discipline children and participate in children’s learning (parenting styles and parental support), and inherent factors of the child’s sex. Parenting styles may also affect children’s outcomes. The main purpose of this study was to determine the relationship between parenting styles, parental involvement and preschool children’s intellectual ability. Besides, this study also assessed the moderating role of the child’s sex on the relationship between parenting styles and parental involvement among preschool children.